2007
DOI: 10.1002/polb.21187
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic nanofillers in PMMA nanocomposites—An investigation of particle size and dispersion and their influence on nanocomposite properties

Abstract: Mechanical, thermal, and electrical properties of graphite/PMMA composites have been evaluated as functions of particle size and dispersion of the graphitic nanofiller components via the use of three different graphitic nanofillers: ''as received graphite'' (ARG), ''expanded graphite,'' (EG) and ''graphite nanoplatelets'' (GNPs) EG, a graphitic materials with much lower density than ARG, was prepared from ARG flakes via an acid intercalation and thermal expansion. Subsequent sonication of EG in a liquid yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
171
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(186 citation statements)
references
References 67 publications
9
171
1
5
Order By: Relevance
“…A similar result was given by Li and Jeong [8]. In other studies, thermal stability enhancements have been reported for polycarbonate-GNP nanocomposites [29] and poly(methyl methacrylate) as a polymer matrix [30] using the same grade of GNP as used in the current study.…”
Section: Thermal Stabilitysupporting
confidence: 72%
“…A similar result was given by Li and Jeong [8]. In other studies, thermal stability enhancements have been reported for polycarbonate-GNP nanocomposites [29] and poly(methyl methacrylate) as a polymer matrix [30] using the same grade of GNP as used in the current study.…”
Section: Thermal Stabilitysupporting
confidence: 72%
“…Nowadays, most investigated nanofillers are carbon nanotubes (CNT) [1][2][3][4], graphene, a two-dimensional sheet made of sp 2 -hybridized carbon atoms in an extended honeycomb network [5], and graphitic nanofillers [6][7][8][9] made by few layers of graphene (GE), usually indicated as graphite nanoplatelets, graphite nanosheets, graphite nanoflakes or just simply exfoliated or expanded graphite. Reviews are available on polymer nanocomposites (PNC) based on these types of nanofillers [8][9][10][11]. In polymer melts and elastomers, the formation of networks at low nanofiller concentration leads to high values of the dynamic modulus at low strain amplitudes, that goes however along with a pronounced reduction as the strain amplitude increases, phenomenon known as Payne effect [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the glass transition (T g ) temperature either increases or decreases depending on the type of filler, its morphology and the intercrystallite distance. 42,44,58 It is also reported that the T g of PMMA depends upon the degree of tacticity (isotactic, heterotactic, syndiotactic or atactic), thermal history and the type of free radical initiator used during processing. 38,39 Since the ceramics and polymers have different heat capacities, DSC analysis is important to understand the change in the heat flow behavior due to the addition of particles into the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…37 The introduction of fillers into the polymer matrix can also improve the thermal and mechanical properties. [38][39][40][41] It is interesting to note that the addition of small amount of graphite particles (1-5 wt.%) in PMMA has increased the onset degradation temperature of the composite by 20 C. 42 It is also observed that the stability of the composites has increased by 13.5 C as compared to that of pure PMMA, when the very low level (6.1% by weight) of nanosized SiO 2 (23 nm) was added into the PMMA. When the size of the crystallites was further reduced (17 nm), enhancement in the thermal stability has been achieved.…”
Section: Introductionmentioning
confidence: 99%